Polygenic Resilience Modulates the Penetrance of Parkinson Disease Genetic Risk Factors. Issue 2 (24th June 2022) - Liu, Hui; Dehestani, Mohammad; Blauwendraat, Cornelis; Makarious, Mary B.; Leonard, Hampton; Kim, Jonggeol J.; Schulte, Claudia; Noyce, Alastair; Jacobs, Benjamin M.; Foote, Isabelle; Sharma, Manu; ,; et al.
Abstract : Objective: The aim of the current study is to understand why some individuals avoid developing Parkinson disease (PD) despite being at relatively high genetic risk, using the largest datasets of individual‐level genetic data available. Methods: We calculated polygenic risk score to identify controls and matched PD cases with the highest burden of genetic risk for PD in the discovery cohort (International Parkinson's Disease Genomics Consortium, 7, 204 PD cases and 9, 412 controls) and validation cohorts (Comprehensive Unbiased Risk Factor Assessment for Genetics and Environment in Parkinson's Disease, 8, 968 cases and 7, 598 controls; UK Biobank, 2, 639 PD cases and 14, 301 controls; Accelerating Medicines Partnership–Parkinson's Disease Initiative, 2, 248 cases and 2, 817 controls). A genome‐wide association study meta‐analysis was performed on these individuals to understand genetic variation associated with resistance to disease. We further constructed a polygenic resilience score, and performed multimarker analysis of genomic annotation (MAGMA) gene‐based analyses and functional enrichment analyses. Results: A higher polygenic resilience score was associated with a lower risk for PD (β = −0.054, standard error [SE] = 0.022, p = 0.013). Although no single locus reached genome‐wide significance, MAGMA gene‐based analyses nominated TBCA as a putative gene. Furthermore, we estimated the narrow‐sense heritability associated with resilience to PD ( h 2 = 0.081, SE = 0.035, p = 0.0003). Subsequent functional enrichment analysis highlighted histone methylation as a potential pathway harboring resilience alleles that could mitigate the effects of PD risk loci. Interpretation: The present study represents a novel and comprehensive assessment of heritable genetic variation contributing to PD resistance. We show that a genetic resilience score can modify the penetrance of PD genetic risk factors and therefore protect individuals carrying a high‐risk genetic burden from developing PD. ANN NEUROL 2022;92:270–278